Biogeochemical behavior and pollution control of arsenic in mining areas: A review - Zhuang, Fan; Huang, Jingyi; Li, Hongguang; Peng, Xing; Xia, Ling; Zhou, Lei; Zhang, Teng; Liu, Zhenghua; He, Qiang; Luo, Feng; Yin, Huaqun; Meng, Delong (Frontiers in Microbiology, 2023)
Arsenic (As) is one of the most toxic metalloids that possess many forms. As is constantly migrating from abandoned mining area to the surrounding environment in both oxidation and reducing conditions, threatening human health and ecological safety. The biogeochemical reaction of As included oxidation, reduction, methylation, and demethylation, which is closely associated with microbial metabolisms. The study of the geochemical behavior of arsenic in mining areas and the microbial remediation of arsenic pollution have great potential and are hot spots for the prevention and remediation of arsenic pollution. In this study, we review the distribution and migration of arsenic in the mining area, focus on the geochemical cycle of arsenic under the action of microorganisms, and summarize the factors influencing the biogeochemical cycle of arsenic, and strategies for arsenic pollution in mining areas are also discussed. Finally, the problems of the risk control strategies and the future development direction are prospected.